Makna kiblat papat lima pancer masjid pathok negara sebagai wujud spiritualitas Nagari Kasultanan Ngayogyakarta - Aminah, Aminah; Alam, Lukis (Universitas Negeri Yogyakarta, 2024)
The Pathok Negara Mosque has an important meaning in determining the boundaries of the Ngayogyakarta Hadiningrat Sultanate as a dependent state. After the Giyanti Agreement, the Mataram Kingdom in Java was divided into two regions, namely the Surakarta Sunanate and the Ngayogyakarta Hadiningrat Sultanate. As the first Sultan, Sultan Hamengkubuwana I began to build the Keraton as the center of government (Nagari Ngayogyakarta) and borders with the Great State (Negaragung) by building the Pathok Negara Mosque in the four corners. This study examines the meaning of Masjid Pathok Negara as a defense system for a new kingdom at that time. The research method is qualitative by looking directly at each Pathok Negara Mosque, analyzing, redrawing, reviewing data and then interpreting according to the relevant theory. The results obtained show that the meaning of the Pathok Negara Mosque as a state spirituality system is shown from the main function of the mosque as a center for spiritual and cultural development, the concept of kiblat papat limo pancer as a macro-microcosmos concept. The existence of physical forms and spaces in the mosque and the area around the Pathok Negara Mosque is an embodiment of values to maintain the spiritual community from that time until now.